2015
DOI: 10.1007/s00383-015-3828-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of taurine on intestinal recovery following intestinal ischemia-reperfusion injury in a rat

Abstract: Treatment with taurine prevents gut mucosal damage and inhibits intestinal epithelial cell apoptosis following intestinal IR in a rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 33 publications
2
15
0
1
Order By: Relevance
“…Sukhotnik et al studied the effect of taurine on intestinal regeneration in animal models. ey reported that the compound may reduce cell apoptosis, stabilize cell membranes, and exert beneficial effects on the regeneration of intestinal mucosa [133]. Taurine has antioxidant properties which may predispose to relief of inflammation [134].…”
Section: Taurinementioning
confidence: 99%
“…Sukhotnik et al studied the effect of taurine on intestinal regeneration in animal models. ey reported that the compound may reduce cell apoptosis, stabilize cell membranes, and exert beneficial effects on the regeneration of intestinal mucosa [133]. Taurine has antioxidant properties which may predispose to relief of inflammation [134].…”
Section: Taurinementioning
confidence: 99%
“…Sukhotnik et al 86 showed protective effect of Tau on intestinal recovery following intestinal ischemia-reperfusion injury in rats. It is well known that during reperfusion of ischemic tissue reactive oxygen species (ROS) and reactive nitrogen species are generated in excess.…”
Section: Taurinementioning
confidence: 99%
“…Intestinal ischemia is a serious and complex disease that may include acute mesenteric ischemia, chronic mesenteric ischemia, or ischemic colitis . Experimental intestinal IRI is induced by clamping the superior mesenteric artery alone or with the portal vein for a period of 30 min to 2 h, followed by reperfusion . An intestinal IRI model was (Figure ) successfully employed to study novel polymeric nanocarriers for potentially toxic and poorly water‐soluble pharmaceutical agents, such as indomethacin and simvastatin …”
Section: Animal Models For Studying Cell‐assisted Drug Deliverymentioning
confidence: 99%